Form follows function? Evidence on tax savings by multinational holding structures - Daniel Dreßler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
I provide evidence on the group structures of multinationals and analyze to what extent these structures are tax efficient. While the corporate income tax can hardly be avoided if a subsidiary is active in a country, withholding taxes depend on the structure in which the subsidiary is embedded. By vertically inserting holding companies or adjusting the superior/subordinate relationship of subsidiaries, multinationals can often influence their total tax burden, especially regarding the repatriation of profits by means of dividends. I analyze group structures across 58 countries in the years 1996 to 2008 using the MiDi database provided by the German Central Bank (Deutsche Bundesbank). The results show that a higher withholding tax between two members of a group located in different countries increases the probability of indirect participation. However, in about half of the observations, the existence of an intermediate subsidiary does not lower the overall tax burden, and in 5% of the cases the tax burden on repatriated profits with such a holding company is even higher than without it. Although group structures generally seem to be tax driven, there are non-tax influencing factors which sometimes prevail. Besides drivers of the vertical company structure, I provide evidence of a horizontal driver: once a form of group taxation is available, groups seem to spread their national investments across more subsidiaries.
Keywords: F23; H25; H32; 330; Corporate Taxation; Foreign Direct Investment; Holdings; Multinational Firms; Withholding Taxes